Fomentar el pensamiento crítico en los estudiantes de octavo año de educación básica paralelos A, B, C del instituto tecnológico superior Dr. José Ochoa León de la ciudad de Pasaje provincia de El Oro. 2012, para lograr un mejor desenvolvimiento escolar. - Pacheco Barrera, Manuel Alberto (2012)
Many students are hesitant to develop in the educational field for shame, for fear of making mistakes, being the subject of ridicule from their peers who are inclined to condemn these actions which are supposedly as " wanting to excel " low self-esteem because they believe they are not able to know the answers or how to express them.